2009
DOI: 10.1007/s11249-009-9466-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Tactile Sensation and Friction Signals in Cosmetic Foundation

Abstract: A tribometer was developed to simulate friction phenomena occurring when human fingers are rubbed together in order to acquire the tactile sensation of applying cosmetic foundation. The tribometer utilizes silicone-rubber surfaces with compliance comparable to that of human fingerpads; these surfaces are lubricated by 10 types of samples simulating cosmetic foundation. To characterize the samples, seven types of feature quantities are introduced from friction signals acquired in three types of sliding tests. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Instead of investigating an active participant assessing a product against a substrate, an alternative approach is to artificially simulate a finger rubbing action and to measure the frictional-and other-phenomena that occur during such rubbing [62,63]. In effect these are "artificial finger" devices.…”
Section: Instrumental Measurements From Live and Simulated Touchmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of investigating an active participant assessing a product against a substrate, an alternative approach is to artificially simulate a finger rubbing action and to measure the frictional-and other-phenomena that occur during such rubbing [62,63]. In effect these are "artificial finger" devices.…”
Section: Instrumental Measurements From Live and Simulated Touchmentioning
confidence: 99%
“…In effect these are "artificial finger" devices. The tribometer reported in the 2009 study [63] was used to measure the temporal evolution of friction which was then characterized by seven parameters such as the static friction coefficient, kinetic friction coefficient and amplitudes of vibration. Measurements were made on 10 product formulations, all consisting of mica and acrylic particles in oil.…”
Section: Instrumental Measurements From Live and Simulated Touchmentioning
confidence: 99%
“…As indicated, the intensity of firing of each mechanoreceptive unit differed for different samples. Some previous studies were conducted to estimate tactile sensation using vibration information, but they only used physically featured qualities, such as the frequency of resonance vibration [ 19 ], and the peak value of vibration [ 9 ]. Neither of these markers was related to the firing nature of the mechanoreceptive units.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have focused on the effects of the friction properties on the tactile feel during the application of cosmetic products. Horiuchi et al showed that static and kinetic friction coefficients are not always the dominant factors in determining the comfort feel when subjects rub powder foundation with their fingers 3 . Sukigara et al showed that the smooth feel of cosmetic sponges depends on the surface roughness, density, and mechanical properties of the sponge 4 .…”
Section: Introductionmentioning
confidence: 99%